2008
DOI: 10.1007/s11250-008-9222-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-vaccination antibodies profile against Peste des petits ruminants (PPR) virus in sheep and goats of Punjab, Pakistan

Abstract: A total of 70 sheep and 330 goats were selected randomly. All the animals were kept under same housing and management conditions. Serum samples were collected from all the animals and tested for the presence of antibodies against Peste des petits ruminants (PPR) virus using competitive ELISA (cELISA). All the animals were found negative showing percentage inhibition (PI) values <50. The animals were vaccinated against PPR with Nig/75/1 strain vaccine of PPR Serum samples were collected from randomly selected 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 14 publications
7
21
1
Order By: Relevance
“…In another study the case fatality rates were 46.9% and 34.4% in goat and sheep populations affected by PPRV, respectively (Shankar et al, 1998). This observation is consistent with the previous reports of Khan et al, 2007 andAbubaker et al (2008) who reported that the PPR disease outbreaks were more severe in goats than sheep. The increased severity of PPRV infection in goats than sheep could be attributed to marked immunosuppression in infected goats (Rajak et al, 2005) that occurred through inhibition of leukocyte proliferation (Heaney et al, 2002), apoptosis of peripheral blood mononuclear cells (Mondal et al, 2001) and/or downregulation of CD46 (Galbraith et al, 1998).…”
Section: Discussionsupporting
confidence: 94%
“…In another study the case fatality rates were 46.9% and 34.4% in goat and sheep populations affected by PPRV, respectively (Shankar et al, 1998). This observation is consistent with the previous reports of Khan et al, 2007 andAbubaker et al (2008) who reported that the PPR disease outbreaks were more severe in goats than sheep. The increased severity of PPRV infection in goats than sheep could be attributed to marked immunosuppression in infected goats (Rajak et al, 2005) that occurred through inhibition of leukocyte proliferation (Heaney et al, 2002), apoptosis of peripheral blood mononuclear cells (Mondal et al, 2001) and/or downregulation of CD46 (Galbraith et al, 1998).…”
Section: Discussionsupporting
confidence: 94%
“…The odds of being seropositive were 1.06 (95% CI 0.89-1.25) in goats than in sheep, which implies there is no difference between the species. This is in contradiction with some studies, including one carried out in Tanzania [11], which reported a higher seroprevalence in goats than in sheep and linked it to higher fecundity in goats compared to sheep [2,18,22]. Other studies have reported higher seroprevalence in sheep than goats, attributing it to lower number of sheep sampled or due to the fact that goats are often affected more severely by the disease hence die prior to sampling [19,23].…”
Section: Discussionmentioning
confidence: 85%
“…The small ruminants play an important role in sustainable agriculture and for poverty alleviation in the country. The existence of PPR has been recognized in Pakistan since 1991 on the basis of clinical signs (Pervez et al, 1993;Athar et al, 1995;Amjad et al, 1996 andTahir et al, 1998) and on the basis of laboratory confirmation (Khan et al, 2007;Abubakar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%